HIV viraemia during hepatitis B vaccination shortens the duration of protective antibody levels. Issue 3 (14th January 2015) - O'Bryan, TA; Rini, EA; Okulicz, JF; Messner, O; Ganesan, A; Lalani, T; Bavaro, MF; O'Connell, RJ; Agan, BK; Landrum, ML
<x xml:space="preserve">Abstract</x> Objectives Individuals with HIV infection often have early waning of protective antibody following hepatitis B virus (HBV) vaccination. HIV viraemia at the time of vaccination may limit the durability of serum anti‐HBV surface antibody (HBsAb) levels. We investigated the relationship of HIV plasma viral load (VL) and duration of HBsAb among vaccinees enrolled in the US Military HIV Natural History Study. Methods We included in the study participants who had no history of prior HBV infection, who had received all HBV vaccine doses after HIV diagnosis, and who had demonstrated an initial vaccine response, defined as HBsAb ≥ 10 IU/L. Responders were retrospectively followed with serial HBV serology from the time of the last vaccine dose until the development of waning (HBsAb < 10 IU/L) or the last HBsAb measurement. Time to and risk for waning were evaluated with Kaplan−Meier survival methods and Cox proportional hazards models, respectively. Results A total of 186 initial vaccine responders were identified. During 570 person‐years of observation, HBsAb waned in 52 of 186 participants (28%). The cumulative proportion maintaining HBsAb ≥ 10 IU/L was 83% at 2 years and 56% at 5 years. Participants with an undetectable VL [hazard ratio (HR) 0.37; 95% confidence interval (CI) 0.18–0.76] or with detectable VL of ≤ 10 000 copies/mL (HR 0.46; 95% CI 0.21–1.00) had reduced risk of waning. Other factors including age, number of vaccine doses, CD4 count, and receipt of highly active antiretroviral therapy (HAART) were not significantly associated with risk of waning HBsAb. Conclusions Undetectable or low HIV VL at the time of HBV vaccination is associated with greater durability of vaccine response in patients with HIV infection.